2004
DOI: 10.1021/jp045246v
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Light-Energy Conversion Efficiency by Multi-Porphyrin Arrays of Porphyrin−Peptide Oligomers with Fullerene Clusters

Abstract: Organic photovoltaic cells using supramolecular complexes of porphyrin-peptide oligomers (porphyrin-functionalized alpha-polypeptides) with fullerene demonstrate remarkable enhancement in the photoelectrochemical performance as well as broader photoresponse in the visible and near-infrared regions by increasing the number of porphyrin units in alpha-polypeptide structures. A high power conversion efficiency (eta) of 1.3% and a maximum incident photon-to-photocurrent efficiency (IPCE) of 42% were attained using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
133
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 37 publications
0
133
0
Order By: Relevance
“…107,117 It should be emphasized here that the simple substituent of methoxy groups onto the meta-positions of the meso-phenyl groups on the porphyrin ring is responsible for the efficient photocurrent generation, which is much superior to the systems from the more complex, time-consuming pre-organized porphyrin molecular assemblies and C 60 . [107][108][109][110][111][112][113][114][115][116]203,204 Various spectroscopic and surface analyses showed that the molecular arrangement of 19a and C 60 composite clusters on the SnO 2 electrode was similar to the molecular packing in a single crystal of 19a Á 2C 60Á toluene.…”
Section: Itomentioning
confidence: 95%
See 1 more Smart Citation
“…107,117 It should be emphasized here that the simple substituent of methoxy groups onto the meta-positions of the meso-phenyl groups on the porphyrin ring is responsible for the efficient photocurrent generation, which is much superior to the systems from the more complex, time-consuming pre-organized porphyrin molecular assemblies and C 60 . [107][108][109][110][111][112][113][114][115][116]203,204 Various spectroscopic and surface analyses showed that the molecular arrangement of 19a and C 60 composite clusters on the SnO 2 electrode was similar to the molecular packing in a single crystal of 19a Á 2C 60Á toluene.…”
Section: Itomentioning
confidence: 95%
“…However, preparation of such three-dimensionally pre-organized molecules is generally difficult and unlikely to be realistic for the future technological applications. 16,17,[107][108][109][110][111][112][113][114][115][116]118,203,204 Therefore, it is highly desirable to exploit a supramolecular photoelectrochemical device consisting of simple, preprogrammed self-assembling porphyrin and C 60 single component composites, which exhibit efficient photocurrent generation as a result of segregated nanoarrays of porphyrin and fullerene on SnO 2 electrodes.…”
Section: ·-mentioning
confidence: 99%
“…14).These supramolecular devices behave as organic photovoltaic cells and demonstrate remarkable enhancement in the photoelectrochemical performance as well as broader photoresponse in the visible and near-infrared regions with increasing the number of porphyrin units in a-polypeptide structures. These results clearly show that the formation of molecular assembly between fullerene and multi-porphyrin arrays with a polypeptide backbone controls the electron-transfer efficiency in the supramolecular complex, which is essential for the light-energy conversion [90].…”
Section: Porphyrinsmentioning
confidence: 74%
“…14. A supramolecular consist of fullerene and multi-porphyrin arrays for the lightenergy conversion [90].…”
Section: Porphyrinsmentioning
confidence: 99%
“…By changing the dendrimer's structure and generation, optimization of efficiency in light energy conversion might become possible. Hasobe et al similarly demonstrated that multi-porphyrin polymer arrays of porphyrin-peptide oligomers with fullerene showed remarkable enhancement in the photoelectrochemical performance [85]. In their system, a broader photoresponse in the visible and near-infrared regions was achieved by increasing the number of porphyrin units in α-polypeptide structures.…”
Section: Assembly With Materialsmentioning
confidence: 99%